(3TQM GdbOhQi ddCbWYs - (3CHh fUQ CMeO Hf eMeO Hf eMeO GdHZOGOj, GdGbWY,J (B474 (3g` s
(3ChdgG (B:s
(3jHJOF HcJGH GdSQbI hbWGY GdWQb s
(3BNQgG (B:s
(3jfJgi HHGH ai GdejQGK s
(3Ydjg Jedc djhSa GdYeQj Hf EHQGgje GdMfaj SfI (B776(3g`s
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B213s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs